Physiological concepts in physical education and sports training: stress, homeostasis and allostasis - Tácito Pessoa de Souza Junior; Benedito Pereira (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n2p206 The objective of this review article is to discuss the concepts of stress and homeostasis (homeos = equal; stasis = stable) and to expose their limitations on the basis of recent evidence demonstrating that the supposed internal stability of living organisms is merely apparent, and is even independent of environmental factors. This internal instability is often observed by researchers investigating circadian rhythms (hormone secretion), temporal series (heart rate) and behavior (hunger and satiety), who argue in favor of substituting the theory of homeostasis by the concept of allostasis (allo = different; stasis = stable). Indeed, these researchers suggest that the objective of regulation and control is not stability. There are two consequences for Physical Education and Sport if allostasis is accepted as a physiological paradigm: 1. Selye's concept of stress requires a new defi nition and interpretation, with a clear impact on the concept of load and overload; 2. Noakes' central governor hypothesis to explain the fatigue resulting from intense physical exercise loses its relevance, as will be discussed in this paper. Furthermore, it is very diffi cult for the model of stability by staying the same to explain why performance is improved by physical training or why we have a predisposition for this type of recognizedly anti-homeostatic activity. We intend to demonstrate the possibility that the allostatic concept of stability through change can explain these contradictions.